2017
DOI: 10.1177/2054358116688228
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Predictive Model for Graft Loss Following Acute Kidney Injury in Kidney Transplant Recipients

Abstract: Background:Acute kidney injury (AKI) is common in the kidney transplant population.Objective:To derive a multivariable survival model that predicts time to graft loss following AKI.Design:Retrospective cohort study using health care administrative and laboratory databases.Setting:Southwestern Ontario (1999-2013) and Ottawa, Ontario, Canada (1996-2013).Patients:We included first-time kidney only transplant recipients who had a hospitalization with AKI 6 months or greater following transplant.Measurements:AKI wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…However, these patients still have increased risk compared to patients without AKI. These results confirm the results of Molnar et al and are in line with the observation that poor graft function at discharge is associated with a poor long‐term graft survival in patients with delayed graft function (DGF) . The increased risk despite the reversibility of AKI is consistent with the results of Uchino, who found increased mortality in patients with a reversible transient GFR reduction regardless of the etiology or the treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, these patients still have increased risk compared to patients without AKI. These results confirm the results of Molnar et al and are in line with the observation that poor graft function at discharge is associated with a poor long‐term graft survival in patients with delayed graft function (DGF) . The increased risk despite the reversibility of AKI is consistent with the results of Uchino, who found increased mortality in patients with a reversible transient GFR reduction regardless of the etiology or the treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, AKI has a borderline association with worse prognosis (HR: 1.71, 95% CI: 0.99‐2.58) when it occurs during the first 3 months and has more deleterious effect of prognosis when occurring later than 3 months post‐transplantation. A similar result was observed in the study of Molnar et al of kidney transplanted inpatients with AKI . A possible explanation for this intriguing finding may derive from the earlier and more intensive treatment usually given in the setting of early‐onset AKI among kidney‐transplanted patients, as compared to late‐onset AKI.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…transplant studies showing that deceased donor transplantation is associated with AKI (22,44). Several studies reported a higher incidence of AKI in subjects with CKD and a higher risk of developing AKI with advanced CKD (20)(21)(22)45,46).…”
Section: Discussionmentioning
confidence: 99%